Effect of Inflation, Exchange Rate, and Interest Rate on the Composite Stock Price Index - Siti Kholijah; Amimah Qodari; Yolanda Sari; Pandu Adi Cakranegara; Agnes Soukotta (Budapest International Research and Critics University, 2022)
The purpose of this research is to discuss effect of inflation, exchange rate, and interest rate on the composite stock price index. The type of research used in this research is casual research. This study uses quantitative data with the type of time series data. Samples taken from 2018 to the end of 2021, in the form of monthly data, the data is secondary data that has been validated and issued directly from the official website. The method of analysis used multiple regression analysis. The results show that inflation has a positive and significant effect on the composite stock price index. Exchange rate has a positive and insignificant effect on the composite stock price index. Interest rate has a positive and significant effect on the composite stock price index.